IMPLEMENTASI STRATEGI INQUIRY GURU PAI DALAM MENINGKATKAN CRITICAL THINKING SISWA KELAS VI DENGAN KONSEP HIGHER ORDER THINKING SKILLS (HOTS) DI SDN 06 MENSERE TAHUN PELAJARAN 2023/2024 - Ikhlas Ikhlas; Aslan Aslan; Mutazam Mutazam (ADIBA : JOURNAL OF EDUCATION, 2024)
The aims of this research are: 1) To describe the implementation of PAI teacher inquiry strategies in improving the critical thinking of class VI students at SDN 06 Mensere. 2) To describe the application of the Higher Order Thinking Skills (HOTS) concept in improving the critical thinking abilities of class VI students at SDN 06 Mensere. Researchers used a qualitative approach with descriptive research type. The data collection techniques used were interviews, observation and documentation. The data analysis techniques used are data reduction, data display, and conclusions. The results of the research show that: 1) The implementation of PAI teacher inquiry strategies in improving the critical thinking of class VI students at SDN 06 Mensere is very good, starting with making a plan by determining the problems that will be solved by students and then implementing the inquiry strategy by giving problems to students to solve and carry out evaluations by looking at the development of students' critical thinking both objectively and in the grade book. 2) Implementing the Higher Order Thinking Skills concept for PAI teachers by creating HOTS-based questions and then handing them over to students to work on and seeing the effectiveness of applying the HOTS concept by looking at the final results of the assignments that students have completed.